The Extroverted–Introverted Students with Their Second Language Acquisition Process - Zai, Tian Best Dion; Erfiani, Ni Made Diana; Laba, I Nengah; Awololon, Yohanes Octavianus Lesu (Lexeme : Journal of Linguistics and Applied Linguistics, 2025)
This study aims to investigate the relationship between introvert and extrovert personality types and their preferred methods for learning English speaking skills among student of the ULW department at SMK Wira Harapan. The study was motivated by observation that different student exhibit varying preferences in learning strategies that may or may not align with their personality traits. This study using mix-method, qualitative research used interviews and quantitative use personality tests based on the Eysenck Personality Questionnaire to categorize students’ personalities. Data were analyzed by classifying students’ learning methods according to Brown’s (2008) speaking categories: imitative, intensive, responsive, interactive, and extensive. The result show that extrovert student predominantly used interactive and responsive methods, involving others through conversations with friends, teacher, tourists, or strangers. Introvert student tended to prefer imitative and intensive methods, practicing speaking alone by repeating lyrics, shadowing film dialogues, or reading aloud. However, there were exceptions: some extrovert student preferred learning alone with extensive and imitative methods, while some introverts occasionally engaged in brief interactions. These findings indicate that learning methods are influenced not only by personality but also by personal motivation and learning context. The study concludes that interactive methods are most effective for improving student’ speaking abilities, as most student who achieved better fluency practiced English by directly interacting with others, it suggested that teacher more interactive activities in the classroom to boost students’ confidence and speaking competence.